Uma descrição do humano no Leviathan - Ismar Dias de Matos (2002)
This dissertation intends to be a description of the human being present in Leviathan and aims to evidence the idea that Thomas Hobbes, starting with the canons of the materialistic-mechanicistic science, building up an anthropology to sustain its political theory , which is the major purpose of his work. The hobbesian being is presented as an impair individual in the world, because he possesses the power of creating a language. It is because of the language that man turns to be a craftsman and is capable to create an artificial being (the State) to guarantee his security and necessary peace for his complete human development. This way, creating a State, man is architecting his self-construction, thus being a builder of his own humanity.